Exploring Students’ Motivation and Vocabulary Achievement through Labeling Method - Erwin Kainta; Jerry Elfindo Rombot (Vision: Journal for Language and Foreign Language Learning, 2020)
Motivation provides energies for students to decide efforts and they pursue it hardly. It is important to build students' motivation in learning English. Researcher's preliminary study toward the fourth grade of MIS Azzikir Kalialia in February 2019 indicated students' motivation was in the low category, while the result of the pre-test showed 35% of students did not achieve success standard in learning vocabulary. The objectives of the study is to explore how students are motivated by using labelling method and to improve students' vocabulary achievement by using labelling method. The number of the subject is 20 students. The instruments are the test, questionnaire, and observation under the Classroom Action Research method. After treatment, the questionnaire indicates students' motivation in high motivation and whole students achieve the standard of vocabulary achievement. Therefore, the labelling method promotes a way of English language teaching to build students' motivation and to improve vocabulary achievement in elementary grade.